Worldwide prevalence of molar-incisor hypomineralization: A literature review - Norailys Pérez Navarro; Burak Buldur (Arbu Academic Publishing, 2024)
Molar-incisor hypomineralization (MIH) is a qualitative enamel defect with a multifactorial etiology, affecting at least one permanent first molar and often associated with permanent incisors and other teeth. MIH is prevalent worldwide, particularly among children under 10 years of age. However, its prevalence rates vary significantly even within the same country. This study aimed to determine the global prevalence of MIH from 1987 to 2023, focusing on children aged 3 to 18 years, using the 2003 EAPD classification. A comprehensive literature review was conducted using PubMed, MEDLINE, CENTRAL, Web of Science, SciELO, LILACS, and Google Scholar, covering studies from 1987 to July 2023 that included sample sizes of more than 1,000 children. A total of 80 studies met the inclusion criteria, with most participants aged between 6 and 12 years. Of these studies, 69 (86.2%) utilized the 2003 EAPD classification. Globally, 17,980 children out of 179,800 examined presented MIH, resulting in a prevalence of 9.4%. Regional prevalence varied: in Asia, 8,812 out of 81,954 children (10.7%) had MIH; in Africa, 344 out of 6,904 children (4.9%); in America, 2,193 out of 12,324 children (17.7%); and in Europe, 6,631 out of 90,042 children (7.3%). The American region reported the highest prevalence of MIH at 17.7%, while Europe and Asia showed similar rates close to the global prevalence (7.3% and 10.7%, respectively). Africa reported the lowest prevalence at 4.9%, but the number of studies conducted there was limited. Overall, MIH has a moderate global incidence with significant regional variations.